Negative Mood Induction Increases Choice of Heroin Versus Food Pictures in Opiate-Dependent Individuals: Correlation With Self-Medication Coping Motives and Subjective Reactivity - Hogarth, Lee; Hardy, Lorna; Bakou, Alexandra; Mahlberg, Justin; Weidemann, Gabrielle; Cashel, Sharon; Moustafa, Ahmed A. (Frontiers in Psychiatry, 2019)
Acute growth in negative affect is thought to play a major role in triggering relapse in opiate dependent individuals. Consistent with this view, three lab studies have demonstrated that negative mood induction increases opiate craving in opiate dependent individuals. The current study sought to confirm these effects with behavioural measure of heroin-seeking, and test whether the effect is associated with self-reported opiate use to cope with negative affect and subjective reactivity to mood induction. Participants were heroin dependent individuals engaged with treatment services (n=47), and control participants (n=25). Heroin users completed a questionnaire assessing reasons for using heroin: negative affect, social pressure, and cued craving. Baseline heroin choice was measured by preference to enlarge heroin versus food thumbnail pictures in two-alternative forced choice trials. Negative mood was then induced by depressive statements and music before heroin choice was tested again. Subjective reactivity was indexed by negative and positive mood reported at the pre-induction to post-test timepoints. Heroin users chose heroin images more frequently than controls overall (p=.001) and showed a negative mood induced increase in heroin choice compared to control participants (interaction p<.05). Mood induced heroin choice was associated with self-reported heroin use to cope with negative affect (p<.05), but not social pressure (p=.39) or cued craving (p=.52), and with subjective mood reactivity (p=.007). These data suggest that acute negative mood is a trigger for heroin-seeking in heroin dependent individuals, and this effect is pronounced in those who report using heroin to cope with negative affect, and those who show greater subjective reactivity to negative triggers. Interventions should seek to target negative coping motives to build resilience to affective triggers for relapse.